2007
DOI: 10.1121/1.2737747
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the backscatter coefficient of formalin-fixed ovine myocardium

Abstract: The objective of this study was to measure the backscatter coefficient of formalin-fixed myocardial tissue as a function of angle of insonification relative to the myocardial fiber direction. Backscatter measurements were performed on eight cylindrical formalin-fixed lamb myocardial specimens and compensated for attenuation and diffraction effects to determine the backscatter coefficient. The backscatter coefficient at 5 MHz was found to be maximum for insonification perpendicular to the predominant myofiber o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…It is necessary to determine a rational means of segmental differentiation. Several investigations demonstrated that the echogenic reflection arises when insonification is perpendicular to the predominant myofiber orientation, and disappears for parallel insonification . Our study also showed that different acquisition angles had influence on the reflection.…”
Section: Discussionsupporting
confidence: 68%
“…It is necessary to determine a rational means of segmental differentiation. Several investigations demonstrated that the echogenic reflection arises when insonification is perpendicular to the predominant myofiber orientation, and disappears for parallel insonification . Our study also showed that different acquisition angles had influence on the reflection.…”
Section: Discussionsupporting
confidence: 68%
“…Their work is in keeping with our notion that the intensity of the backscatter is increased when the cardiomyocytes are perpendicular to the direction of the ultrasonic beam . Their results also endorsed the findings of several earlier studies of both the heart and human tendons . The similarity between echocardiography, and structure tensor analysis from microcomputed tomography, and diffusion tensor imaging in our study reinforces this viewpoint.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, several studies from our Laboratory and others have demonstrated the profound effects of anisotropic myocardial structure can have on measured ultrasonic properties. (Baldwin et al 2006; Hoffmeister et al 1995; Madaras et al 1988; Marutyan et al 2006; Mottley and Miller 1988; Mottley and Miller 1990; Verdonk et al 1996; Verdonk et al 1992; Yang et al 2007) These anisotropic properties of the myocardium can greatly influence the observed apparent backscatter in echocardiographic images. (Aygen and Popp 1987; Holland et al 2005; Holland et al 1998; Recchia et al 1995)…”
Section: Introductionmentioning
confidence: 99%